Anomalous interference and hybrid filtration for stochastic processes in observation channels with memory; Automatic Control and Computer Sciences; Vol. 35, Iss. 5 - Demin N. S. Nikolas S. (2001, 2001)
Previous results [1, 2] are extended to the case of backup in digital observation channels with memory. The filtration accuracy is related to the backup order. A study is made on how the filtration accuracy in an ideal backup channel with memory differs from that in an ideal backup channel without memory.